Psychological Wellbeing of Parents Who Have Children with Cancer at Ambu Cancer Fighter House Foundation - Rukmasari, Ema Arum; Agusti, Adriyan Dwi; Ramdhanie, Gusgus Ghraha; Kosim (International Journal of Science and Society, 2023)
Cancer is a chronic disease that requires intensive treatment. While undergoing treatment, parents of children with cancer are faced with various problems that interfere with their mental health, which can delay the child's treatment process. The aim of this research is to find out the psychological well-being of parents who have children with cancer at the Ambu Cancer Fighters Home Foundation. This research used quantitative descriptions, involving 40 parents who had children with cancer at the Ambu Cancer Fighters Home Foundation. The number of samples taken in this research was 37. The research sampling technique was accidental sampling. The Ryff psychological well-being scale questionnaire was used as an instrument. The data analysis used was univariate. More than half of the respondents had a high level of mental well-being (59.5%), and less than half of the respondents had a low level of mental well-being (40.5%). High levels of psychological well-being indicate that parents are able to face various challenges in caring for their children. Efforts are needed to improve the psychological well-being of parents so they can provide maximum care to their children.